Identification of Alteration Zones Based on Resistivity and Induced Polarization Geoelectric Survey - Hana Raihana; Jesika Erni Elfrita Sinaga; Adinda Gusti Cahyani; Halauddin Halauddin; Suhendra Suhendra; Anggiat Hutauruk; Nanang Sugianto (Jambura Geoscience Review, 2023)
Air Putih, Lebong Regency's geothermal field, is near gold mining. The relationship between the two can be illustrated in the type of rock alteration. The study aims to identify the rock alteration zone caused by the Air Putih, Lebong Regency geothermal system. It was described by the correlation of rocks' resistivity and chargebility values based on geoelectric measurement. Two tracks spread along the Air Putih tour, with a track length of 240 meters, were used to see variations in resistivity and chargeability values and the depth of geothermal potential due to deeper current penetration to determine the alteration zone in the study area. The results of field measurements are in the form of 2D models processed with Res2DinvX64 software. According to analysis, the subsurface rock lithology in the research area is relatively the same because the location of the two measurement lines is still close together; namely, there are wet valley rocks and alterated rock layers. Pores cause rock layers found in conductive areas in the rock filled with fluid or water at high temperatures. It is evidenced by the detection of manifestations on the surface in the form of warm soil, warm rocks, steamy soil, and small holes containing water grains. The higher the temperature and pressure, the lower the value of rock-specific resistance. At the Air Putih tourist area of Lebong Regency, it is found that it is a zone of prophylitic alteration containing several minerals of andesite lava, breccia, tuff, and soil.